Spectrum of musculoskeletal disorders in Nigerians with types 2 diabetes mellitus: prevalence and predictors - H. Olaosebikan; A. Azenabor; R. Akintayo; O. Adelowo; A. Ogbera; A. Brodie-Mends (PAGEPress Publications, 2020)
Musculoskeletal (MSK) conditions are more frequently found among patients with diabetes mellitus (DM) than in the non-diabetics. Despite several reports outside Africa, they have been under-studied among Africans. This study aimed to assess the overall prevalence and predictors of MSK conditions in Nigerian with types 2 diabetes mellitus (T2DM). A total of 268 adult with T2DM and 268 non-diabetic controls were recruited. All study subjects had their socio-demographics and clinical parameters obtained using interviewer-administered questionnaire. Musculoskeletal conditions among study subjects were classified using validated criteria and case definitions. Musculoskeletal disorders (MSKD) were significantly more frequent amongst subjects with DM (56% vs 22%, OR=4.5 p=0.001). Osteoarthritis (9.3% vs 4.1%, p=0.016), lumbosacral spondylosis (5.6% vs 2.2%, p=0.045), limited joint mobility (13.8% vs 5.6%, p-0.001), adhesive capsulitis (4.5% vs 1.5%, p-0.042) and rotator cuff tendinitis (3.7% vs 0.4%, p=0.006) were more frequent in DM subjects than in controls. Logistic regression showed that age (OR=2.1, CI=1.5-2.6) and waist circumference (OR=3.0, CI=2.6- 3.4) are independent predictors of MSKD among patients with diabetes. This study found higher prevalence of MSKD among diabetic subjects. It also identified certain factors associated with MSKD among patients with diabetes mellitus.